2022
DOI: 10.3390/vaccines10040535
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of Health Care Workers and Medical Students towards Vaccination against COVID-19

Abstract: The role of medical personnel in promoting vaccination and pro-health attitudes seems to be of key importance for protection against COVID-19. The aim of the study was to assess the attitudes of health care workers and students of medical faculties towards preventive vaccinations against COVID-19. A cross-sectional online self-administered survey was conducted among 497 people. The questions concerned attitudes towards vaccination as well as concerns about the side effects of the vaccine and contracting COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…A greater positive attitude towards the COVID-19 vaccine was found in our study than in Obarisiagbon OE et al, in Nigeria; Alle YF et al, in Ethiopia; and Khan ZA et al, in Pakistan [ 22 , 24 , 25 ]. A similar positive attitude was reported in the study conducted by Jankowska-Polaska B et al in Poland [ 26 ].…”
Section: Discussionsupporting
confidence: 87%
“…A greater positive attitude towards the COVID-19 vaccine was found in our study than in Obarisiagbon OE et al, in Nigeria; Alle YF et al, in Ethiopia; and Khan ZA et al, in Pakistan [ 22 , 24 , 25 ]. A similar positive attitude was reported in the study conducted by Jankowska-Polaska B et al in Poland [ 26 ].…”
Section: Discussionsupporting
confidence: 87%
“…Of the 52 included studies, seven [ 30 , 50 , 66 , 69 , 73 , 74 , 76 ] did not report formal VH/VA rates. However, as these studies reported factors associated with intentions to vaccinate, the decision was made to include them for review.…”
Section: Resultsmentioning
confidence: 99%
“…Low perceived personal risk of contracting COVID-19 infection, low vulnerability to severe infection, and belief in natural immunity [ 25 , 36 , 38 , 39 , 43 , 52 , 53 , 55 , 58 , 64 , 66 ] were also found to be associated with VH. Previous history of COVID-19 infection was shown to increase vaccine acceptability in some studies [ 45 , 64 , 67 ]; however, it was also shown to decrease vaccine acceptance [ 39 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding attitudes about vaccination, most healthcare workers, during the first epidemic wave, reported that they were waiting for the release of the vaccine to eliminate the COVID-19 pandemic, have had a vaccination against coronavirus disease, when the vaccine was released, and would recommend vaccination. Globally, HCW had a positive attitude concerning the vaccine against COVID-19 [ 39 ]. Nevertheless, resistance to the vaccine among health workers was particularly high in Greece, with the first surveys at the beginning of the pandemic and before the vaccination campaign, showing only 51.1% positivity to receive the vaccine [ 40 ].…”
Section: Discussionmentioning
confidence: 99%